The construction of Islamic law benefit in the perspective of progressive law - Rozihan Rozihan (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2020)
The law is applied is to reach the benefit of the object subject to the law. The concept of benefit discussed by the scholars of the past up to the time of Al-Syatibi, is the concept of theocentric benefit, namely benefit based on the text, so that the intended benefit must be in accordance with the wishes of the legislators (maqsud al-Syar'i). Based on this, the concept of theocentric benefits must be formulated into anthropocentric benefits. Namely, benefit based on the desire and goodness of the object of law (maqsud al-mukallaf). The progressive law, which is a law that is not bound by the law or in other words the law based on conscience. So, through this progressive law will be able to realize the benefit for the joint.